2D Hexagonal Covalent Organic Radical Frameworks as Tunable Correlated Electron Systems. (4th November 2020) - Santiago, Raul; Alcón, Isaac; Ribas‐Arino, Jordi; Deumal, Mercè; de P. R. Moreira, Ibério; Bromley, Stefan T.
Abstract: Quantum materials hold huge technological promise but challenge the fundamental understanding of complex electronic interactions in solids. The Mott metal–insulator transition on half‐filled lattices is an archetypal demonstration of how quantum states can be driven by electronic correlation. Twisted bilayers of 2D materials provide an experimentally accessible means to probe such transitions, but these seemingly simple systems belie high complexity due to the myriad of possible interactions. Herein, it is shown that electron correlation can be simply tuned in experimentally viable 2D hexagonally ordered covalent organic radical frameworks (2D hex‐CORFs) based on single layers of half‐filled stable radical nodes. The presented carefully procured theoretical analysis predicts that 2D hex‐CORFs can be varied between a correlated antiferromagnetic Mott insulator state and a semimetallic state by modest out‐of‐plane compressive pressure. This work establishes 2D hex‐CORFs as a class of versatile single‐layer quantum materials to advance the understanding of low dimensional correlated electronic systems. Abstract : 2D hexagonally ordered covalent organic radical frameworks (2D hex‐CORFs) tend to exhibit an antiferromagnetic Mott insulating ground state. Through careful theoretical analysis, it is shown that modest out‐of‐plane pressures can be used to dynamically shift these low dimensional materials toward a transition to graphene‐like semimetallicity. 2D hex‐CORFs are thus established as a new class of single‐layer pressure‐tunable correlated materials.